2010
DOI: 10.1093/intimm/dxq063
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte calcium influx characteristics and their modulation by Kv1.3 and IKCa1 channel inhibitors in the neonate

Abstract: Cytokine production in activated T lymphocytes of the term neonate is reduced compared with adults. We aimed to characterize the calcium influx kinetics of activated T lymphocytes in the neonate and to test the functionality and expression of Kv1.3 and IKCa1 lymphocyte potassium channels, important regulators of calcium influx. We isolated lymphocytes from the peripheral blood of nine adults and cord blood of nine term neonates. We measured the calcium influx kinetics with flow cytometry in the T(h)1, T(h)2, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…-response, neonatal T-cells present other functional characteristics distinct from T-cells of the adult (11,23). Now we measured reduced baseline cytoplasmic Ca 2+ levels and reduced Ca Indeed we measured lower mitochondrial mass in neonatal CD4-cells than in those from the adult.…”
Section: +mentioning
confidence: 70%
See 2 more Smart Citations
“…-response, neonatal T-cells present other functional characteristics distinct from T-cells of the adult (11,23). Now we measured reduced baseline cytoplasmic Ca 2+ levels and reduced Ca Indeed we measured lower mitochondrial mass in neonatal CD4-cells than in those from the adult.…”
Section: +mentioning
confidence: 70%
“…We have found that Ca 2+ -response during short-term activation of T-cells is lower in the neonate than in the adult. The immaturity of potassium channels on neonatal cell membrane may be an explanation for this finding (23).…”
Section: +mentioning
confidence: 96%
See 1 more Smart Citation
“…Note that these calculated parameters differ from the parameters that would be recorded during the measurement for each cell: from a single measurement one can only derive a single value for each such calculated parameter. Jakubczak et al;2006, Demkow et al;2009, Toldi et al;2010b, Szalay et al, 2012), t-test (used in Lund-Johansen et al, 1992, paired Wilcoxon-test (used in Schepers et al, 2009;Toldi et al, 2010a, Szalay et al, 2012.…”
Section: Smoothing Methodsmentioning
confidence: 99%
“…We aimed to characterize the calcium influx kinetics upon activation in major T lymphocyte subsets (i.e. Th1, Th2, CD4 and CD8 cells) in the neonate, and its sensitivity to the specific inhibition of Kv1.3 and IKCa1 lymphocyte potassium channels (Toldi et al, 2010b (Adkins, 1999;Cohen et al, 1999). The functional impairment of lymphocyte potassium channels may be of importance in those mechanisms.…”
Section: Lymphocyte Activation and Potassium Channels In The Newbornmentioning
confidence: 99%